Network meta-analysis of pembrolizumab as monotherapy and in combination with chemotherapy for first-line treatment of recurrent or metastatic head and neck squamous cell carcinoma. - Mojebi, Ali; Ramakrishnan, Karthik; Ayers, Dieter; Keeping, Sam; Borse, Rebekah; Chirovsky, Diana (JBES: Brazilian Journal of Health Economics / Jornal Brasileiro de Economia da Saúde)
Pembrolizumab monotherapy or in combination with chemotherapy is approved as first-line treatment in recurrent/metastatic head and neck squamous cell carcinoma (R/M HNSCC) based on improved overall survival (OS) versus EXTREME regimen in the KEYNOTE-048 trial. The clinical outcomes of pembrolizumab were compared with other recommended first-line treatments in R/M HNSCC in this study through a Bayesian network meta-analysis. A systematic literature review was conducted in July 2022, from which six trials that matched the KEYNOTE-048 patient eligibility criteria were included in the network. The OS and progression-free survival (PFS) outcomes were compared in the approved pembrolizumab indication (i.e., total population for pembrolizumab in combination with chemotherapy and combined positive score [CPS] ≥ 1 population for pembrolizumab monotherapy). A significant OS improvement was observed for pembrolizumab in combination with chemotherapy and pembrolizumab monotherapy versus EXTREME regimen (hazard ratio, 95% credible interval: 0.72, 0.60-0.86; 0.73, 0.60-0.88), platinum+5- FU (0.58, 0.43-0.76; 0.58, 0.44-0.78), and platinum+paclitaxel (0.53, 0.35-0.79; 0.53, 0.35-0.81), respectively. A non-significant numeric trend in OS improvement was observed versus the TPEx regimen. PFS was comparable with most first-line treatments and was improved versus platinum+5-FU (0.48, 0.36-0.64; 0.59, 0.45-0.79). Additional analyses in higher CPS subgroups also showed consistent results. Overall, our study results showed an improvement in OS outcomes versus alternative first-line treatments, consistent with the findings of the KEYNOTE-048 trial. These data support using pembrolizumab as a suitable firstline treatment option in R/M HNSCC.